Progress in the application of ovarian and fallopian tube organoids - Yi-Lin Dai; Jin-Song Wei; Jing Xu; Ke Li; Jing Wang; Ran-Ran Cha; Yu Kang (Reproductive and Developmental Medicine, 2021)
As an innovative in vitro culture model, organoids have been established by cell sorting and subsequent culture in three-dimensional culture systems. Organoids can be derived from induced pluripotent stem cells or organ-restricted adult stem cells. Compared with traditional two-dimensional cell culture models and patient-derived xenograft models, organoids possess long-term genetic stability and can better retain the characteristics of source tissues or organs. These advantages have led to the increased use of ovarian and fallopian tube organoids in various fields of research, including cell differentiation and development, establishment of disease occurrence and progression models, tissue regeneration and reconstruction, individual drug screening, immune cell co-culture, and maternal–fetal medicine. This review briefly summarizes the recent progress in the application of ovarian and fallopian tube organoids in the field of obstetrics and gynecology.